Integrated well log and 2-D seismic data interpretation to image the subsurface stratigraphy and structure in north-eastern Bornu (Chad) basin. (September 2016) - Isyaku, Aminu A.; Rust, Derek; Teeuw, Richard; Whitworth, Malcolm
Abstract: Structural and stratigraphic mapping within the Bornu Basin in north east Nigeria was commonly carried out using traditional field geological methods. However, such traditional approaches remain inadequate in the semi-arid region characterised by topographically flat areas and lack of continuous bedrock outcrops that are mostly concealed beneath sand cover. Previous studies in the north-eastern part of the basin carried out using ditch cuttings from few wells and disconnected seismic data were largely inadequate and the resulting stratigraphic analyses were more often generalised. This paper presents an integrated structural and stratigraphic study of the basin using combined subsurface geophysical datasets. A Combined Log Pattern (CLP) method is a well log analysis, which utilises various well log data including gamma ray, resistivity, bulk density and sonic logs to identify lithology and stratigraphic boundaries of subsurface formations. This method is applied to constrain the subsurface stratigraphy of the north-eastern part of the Bornu Basin bordering the Lake Chad. In addition to qualitative combined well log analysis, the time-depth relationship of the sonic log and seismic data was quantitatively determined by tying a well with an intersecting seismic section to validate the stratigraphic facies horizons identified. Four well log facies and their environments of deposition were characterised from the combined well log analysis of the different log types. It is discovered that the Cretaceous basement structural features controlled the deposition of overlying formations in the basin. Without intact core data, the shallower wells were discovered to have bottomed over subsurface horst features while deeper wells penetrated into the basal facies contained mainly within the grabens. Main subsurface structural lineaments in the area include NW-SE, NE-SW and NNW-SSE trending faults, which mainly formed the horst and graben features. Some stratigraphic formations described in previous generalised stratigraphic schemes for the Bornu Basin were herein not found in the north-eastern part of the basin. Highlights: A Combined Log Pattern method for well log analysis is presented. Synergy between multiple well log and seismic for structure and stratigraphic study is established. Combined qualitative and quantitative analysis for subsurface structure and stratigraphy carried out in the Bornu Basin. Deposition in Bornu Basin was controlled by horst and graben system. Gombe Formation and Kerri-Kerri Formation were not deposited in the north-eastern Bornu Basin.